The Life Time Prevalence of Childhood Seizure - P AlizadehTaheri; M Naseri; M Lahooti; M Sadeghi (Tehran University of Medical Sciences, 2009)
"nBackground: Seizure is the most common pediatric neurologic disorder. Epidemiological studies of childhood epilepsy are of importance to compare incidence and prevalence rates, age distribution, inheritance, seizure types, epilepsy syndromes and treatment strategies. Since there is little information about prevalence of childhood seizure in Iran, this study was aimed to determine the life time prevalence of childhood seizure and some of its determining factors in Tehran, Iran."nMethods: In this cross sectional study, 2500 male and female students, aged 12 years or younger, studying in fifth grade of primary schools in district one of Ministry of Education were assessed by filling a preliminary questionnaire. Those who were categorized by the author as having a history of any form of seizure were assessed by a second questionnaire. The clinical form of seizure, the presumptive cause, positive family history and use of anti-convulsant drugs were recorded."nResults: The life time prevalence of seizure was 32/1000 population which was more prevalent in boys .Generalized seizure was the most common clinical form. Approximately 60% of cases reported febrile convulsion as the presumptive cause stated by the physician. Positive family history was reported in 29.6% of cases. Anti epileptic drugs were taken by 54% of students with a positive history of seizure."nConclusion: The results of this study show that the life time prevalence of seizure is relatively high in Iranian community, although the other factors were in concordance with other communities.